Social mobility trends in the Armenian diaspora: ethnosociological study of Armenians in Los Angeles, Tehran and Beirut = Trendy mobilności społecznej w diasporze ormiańskiej: badanie etnosocjologiczne Ormian z Los Angeles, Teheranu oraz Bejrutu - Tanajyan, Lusine (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the article is to reveal the peculiarities of social mobility among Armenians in diaspora communities, which was accomplished by conducting a comparative analysis of the Armenian communities in Los Angeles, Tehran and Beirut. To achieve the aim, the following objectives were set: to identify and compare the socio-professional structures of the three communities; to show the dynamics of inter-and intra-generational social mobility of Armenians in three di?erent ethno-social environments.
Keywords: Armenian Diaspora; social mobility; ethno-social environment; diaspora ormiańska; mobilność społeczna; środowisko etnospołeczne